IL-1-polymorphism and severity of periodontal disease - Pretzl, Bernadette; Sayed, Nihad el; Cosgarea, Raluca; Kaltschmitt, Jens; Kim, Ti-Sun; Eickholz, Peter; Nickels, Katrin; Bäumer, Amelie (Acta odontologica Scandinavica, 2012)
Objective. To determine the association between the interleukin (IL)-1-polymorphism and the severity of periodontal disease prior to active periodontal therapy. Materials and methods. Two hundred and six patients with obtained baseline x-rays were tested for IL-1-polymorphism. Relative bone loss before active periodontal treatment was measured with a Schei ruler and classified in five groups. Descriptive statistics and backward stepwise linear regression analyses were performed. Results. Forty-nine patients with moderate (mChP), 79 with severe chronic (sChP) and 78 with aggressive periodontitis (AgP) were included. Age correlated significantly with bone loss and number of teeth at baseline. Gender, smoking and IL-1-polymorphism were neither associated with bone loss nor with number of teeth prior to treatment. After adjusting for age as well as gender, AgP was significantly associated with more severe bone loss in untreated periodontal disease (p = 0.036). In non-smokers, mean number of teeth prior to active periodontal therapy correlated significantly with presence of IL-1 polymorphism. Conclusion. The IL-1-polymorphism is associated with lower number of teeth in non-smokers with untreated periodontal disease. Untreated AgP is associated with more severe bone loss than untreated ChP.